PARTNERSHIP COMMUNICATION OF BPJS EMPLOYMENT SEMARANG WITH PT. WAE IN OPTIMIZING THE ZERO WASTE PROGRAM - Utomo, Adiatma Yogo; Pandjaitan, Rosmawaty Hilderiah; Putra , Afdal Makkuraga (Universitas prof. Dr. Moestopo (Beragama), 2025)
This research aims to know the communication of the partnership of BPJS Ketenagakerjaan in optimizing the Zero Waste program through the Rapel PT WAE application in the Semarang Region in 2024, along with the obstacles and solutions. This research occurred at the BPJS Ketenagakerjaan Office and the PT WAE Office in Semarang. This study uses a qualitative descriptive method. Data collection techniques use interviews, observations, documentation, and literature studies. This study uses the main theories of CMC, RDT (Relational Dialectics Theory), and Interaction Analysis. The results indicate that communication runs in two directions and is linearly carried out directly face to face and indirectly via email and using WA Group media, by creating the Borobudur tour event, meetings, and joint discussions. The obstacles are 1) differences in policies that are seen by PT WAE where the policy becomes profit oriented 2) External factors where users must compete with scavengers to get materials because of the quantity factor of the provisions of the Rapel officers 3) Lack of socialization and delivery of information appropriately to users for the provisions of garbage pick up from the Rapel officers 4) Communication is not only on one media.